2019
DOI: 10.7554/elife.50747
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of branched-chain amino acids is critical for the activity of TOR signaling in Arabidopsis

Abstract: The target of rapamycin (TOR) kinase is an evolutionarily conserved hub of nutrient sensing and metabolic signaling. In plants, a functional connection of TOR activation with glucose availability was demonstrated, while it is yet unclear whether branched-chain amino acids (BCAAs) are a primary input of TOR signaling as they are in yeast and mammalian cells. Here, we report on the characterization of an Arabidopsis mutant over-accumulating BCAAs. Through chemical interventions targeting TOR and by examining mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 86 publications
2
90
0
1
Order By: Relevance
“…In mammals and yeast, the RAPTOR-independent TORC2 complex regulates actin filamentation through multiple pathways ( Jacinto et al, 2004 ; Loewith et al, 2002 ; Rispal et al, 2015 ; Sarbassov and Kim, 2004 ; Schmidt et al, 1996 ). Recently, a forward genetic screen in Arabidopsis found that a recessive allele of isopropylmalate synthase 1 ( IPMS1 ) promotes actin filamentation in a TOR-dependent pathway ( Cao et al, 2019 ). IPMS1 is the first committed step of leucine biosynthesis; accordingly, ipms1 mutants exhibit broad defects in free amino acid accumulation ( Cao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In mammals and yeast, the RAPTOR-independent TORC2 complex regulates actin filamentation through multiple pathways ( Jacinto et al, 2004 ; Loewith et al, 2002 ; Rispal et al, 2015 ; Sarbassov and Kim, 2004 ; Schmidt et al, 1996 ). Recently, a forward genetic screen in Arabidopsis found that a recessive allele of isopropylmalate synthase 1 ( IPMS1 ) promotes actin filamentation in a TOR-dependent pathway ( Cao et al, 2019 ). IPMS1 is the first committed step of leucine biosynthesis; accordingly, ipms1 mutants exhibit broad defects in free amino acid accumulation ( Cao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ETF/ETFQO pathway has been shown to contribute significant amounts of electrons in stress situations (Ishizaki et al, 2005; Pires et al, 2016). The concomitant increase in BCKAs and particularly BCAAs may contribute to the dwarf phenotype as disruption in BCAA homeostasis has been shown to lead to pleiotropic effects including growth retardation (Cao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals and yeast, the RAPTOR-independent TORC2 complex regulates actin filamentation through multiple pathways (Dos et al, 2004;Jacinto et al, 2004;Loewith et al, 2002;Rispal et al, 2015;Schmidt et al, 1996). Recently, a forward genetic screen in Arabidopsis found that a recessive allele of ISOPROPYLMALATE SYNTHASE 1 (IPMS1) promotes actin filamentation in a TORdependent pathway (Cao et al, 2019). IPMS1 is the first committed step of leucine biosynthesis; accordingly, ipms1 mutants exhibit broad defects in free amino acid accumulation (Cao et al, 2019).…”
Section: The Seedling Tor-regulated Proteome and Phosphoproteomementioning
confidence: 99%
“…Recently, a forward genetic screen in Arabidopsis found that a recessive allele of ISOPROPYLMALATE SYNTHASE 1 (IPMS1) promotes actin filamentation in a TORdependent pathway (Cao et al, 2019). IPMS1 is the first committed step of leucine biosynthesis; accordingly, ipms1 mutants exhibit broad defects in free amino acid accumulation (Cao et al, 2019). While the exact cause remains undefined, the disruption of amino acid metabolism in ipms1 mutants apparently increases cellular TOR activity (Cao et al, 2019;Schaufelberger et al, 2019).…”
Section: The Seedling Tor-regulated Proteome and Phosphoproteomementioning
confidence: 99%
See 1 more Smart Citation